1999
DOI: 10.1086/314752
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Infection during Pregnancy: Intrauterine Growth Retardation and Preterm Delivery in Malawi

Abstract: In sub-Saharan Africa, malaria infection in pregnancy contributes to low birth weight through intrauterine growth retardation (IUGR) and preterm delivery (PTD). It was hypothesized that malaria-associated PTD and IUGR have differing etiologies due to timing of infection. In a prospective cohort of primigravid women enrolled at the antenatal clinic of Mangochi District Hospital in Malawi, the associations were investigated between antenatal or delivery parasitemias and IUGR or PTD. Among 178 singleton deliverie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 11 publications
5
86
2
Order By: Relevance
“…0 % in Zambia [20] and 19 . 7 % in a different region of Malawi [21]. This high incidence clearly indicates a major public health problem with maternal malaria and undernutrition [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…0 % in Zambia [20] and 19 . 7 % in a different region of Malawi [21]. This high incidence clearly indicates a major public health problem with maternal malaria and undernutrition [22].…”
Section: Discussionmentioning
confidence: 99%
“…In The Gambia, placental malaria was also significantly associated with IUGR [31], and in Mangochi, southern Malawi, two studies have shown a significant association between placental malaria and IUGR [21,32]. The exact mechanism leading to IUGR with placental malaria is unclear although placental insufficiency and reduction of oxygen and/or glucose transport to the fetus are likely to play a role.…”
Section: Discussionmentioning
confidence: 99%
“…The odds ratio (95% confidence interval [CI]) for a multiple infection was 3.0 (1.8-5.1) in the category 11-1,000 parasites/l, and 8.0 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) in the category Ͼ 1,000 parasites/l compared with the baseline category of submicroscopic infections. The odds ratio for multiple infection decreased with an increasing number of pregnancies, and was lowest among women with Ն 5 pregnancies.…”
Section: Multiplicity Of P Falciparum Infectionmentioning
confidence: 99%
“…13 In highly endemic areas, apart from children, pregnant women, and primigravidae in particular, are at increased risk of P. falciparum infection and clinical malaria. 14,15 Malaria in pregnancy causes intrauterine growth retardation, low birth weight, and preterm delivery, [16][17][18] significantly contributing to neonatal mortality. 19 This increased susceptibility has been attributed to specific strains of P. falciparum that are able to adhere to placental tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] A few studies have documented other maternal factors associated with adverse pregnancy outcomes in subs Saharan Africa. [13][14][15][16][17][18][19][20] However, there are few data on the examination of multiple determinants of birth outcome and the proportion of adverse birth events ats s tributable to these factors from the study region, partly because of a lack of simple, inexpensive diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%